1990
DOI: 10.1093/geronj/45.4.p128
|View full text |Cite
|
Sign up to set email alerts
|

Is Blood Pressure An Important Variable in Research on Aging and Neuropsychological Test Performance?

Abstract: Regression analyses using Blood Pressure, Age, and the multiplicative effect of Blood Pressure and Age as predictors of performance (on selected tests from the Halstead-Reitan neuropsychological test battery) were done. Three hypotheses were tested with subjects ranging in age from 20 to 72 years of age: (1) blood pressure values predict neuropsychological test performance over a wide range of hypertensive and normotensive blood pressure values; (2) blood pressure predicts performance within the narrower range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
59
4
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 0 publications
8
59
4
1
Order By: Relevance
“…In addition, relatively recent evidence has emerged which associates adverse outcomes in the general population with other HR 16,17 and BP thresholds. [18][19][20][21] Beyond the clinical consequences of alterations in HR and BP, persons with SCI may experience loss of independence and life quality related to the inability to adequately maintain cardiovascular homeostasis; however, until we gain a better understanding of the prevalence of these abnormalities, the development and testing of effective treatment strategies will not be a priority. Therefore, we measured HR and BP during routine annual physical examinations in a sample of veterans with SCI from an urban Veterans Affairs Medical Center.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, relatively recent evidence has emerged which associates adverse outcomes in the general population with other HR 16,17 and BP thresholds. [18][19][20][21] Beyond the clinical consequences of alterations in HR and BP, persons with SCI may experience loss of independence and life quality related to the inability to adequately maintain cardiovascular homeostasis; however, until we gain a better understanding of the prevalence of these abnormalities, the development and testing of effective treatment strategies will not be a priority. Therefore, we measured HR and BP during routine annual physical examinations in a sample of veterans with SCI from an urban Veterans Affairs Medical Center.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to blood pressure (BP), many studies have shown that, over a wide range of BP values and with adjustment for hypertensionrelated complications, both systolic and diastolic BP are inversely related to the level of cognitive performance and longitudinal decline in performance. [1][2][3][4][5][6][7][8][9] The most widely accepted mechanism by which high BP reduces cognitive ability is via its effect on brain structure and function. 10 -16 Hypertension is associated with acceleration of atherosclerosis in the large arteries and is associated with medial thickening of the intracerebral vessels leading to cerebral white matter hypoperfusion and ischemic rarefaction.…”
mentioning
confidence: 99%
“…16 A causal association between higher BP and lower cognition has been suggested because of the observation of a "doseresponse" effect in studies relating BP and cognition. [1][2][3][7][8][9] Both the duration and the magnitude of BP elevation have been related inversely to cognitive performance. 9 However, the use of the duration of hypertension as a marker of the chronic hemodynamic burden posed by high BP is challenged by the lack of precision in identifying the exact date of hypertension onset in epidemiological studies.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Systolic blood pressure (SBP) and diastolic blood pressure (DBP) levels have been inversely related to cognitive performance level. 2,10,11 Moreover, DBP and SBP levels in midlife have been inversely associated with performance levels on cognitive tests administered at later ages. 9,[12][13][14] It is important to determine whether baseline BP values are associated with accelerated cognitive change with advancing age.…”
mentioning
confidence: 99%